Funding and Delivery Models for Modern Energy Cooking Services in Displacement Settings: A Review - Iwona Bisaga; Long Seng To (Energies, 2021)
Cooking with modern energy fuels and technologies has a high potential to positively impact the users’ health and well-being, and make cooking safer and less burdensome for women and girls. To date, there have been numerous interventions targeting improved cooking solutions in displacement settings, but very few which have involved modern energy cooking, such as ethanol, biogas, LPG or electric cooking. They have been largely absent from humanitarian programming due to limited availability, affordability and lack of business models that suit those complex settings. Additionally, energy access services in displacement settings have historically relied primarily on grant-based funding. However, grants are limited to relatively short timeframes which do not align with the long-term needs of the displaced. New ways of funding energy access in displacement settings, and particularly modern energy cooking services, are urgently needed to address the scale of the challenge as the number of displaced surpassed 80 million in 2020, with close to 90% having little or no access to adequate cooking fuels and technologies. In this paper, we review modern energy cooking in displacement settings and the common ways of funding and delivering them. We argue that new ways of funding and delivering energy access in displacement settings are urgently needed to address the scale of the challenge and to facilitate transitions to modern energy cooking fuels and technologies, in line with Sustainable Development Goal 7 and the principle of ‘leaving no one behind’.